2014
DOI: 10.7150/ijms.8096
|View full text |Cite
|
Sign up to set email alerts
|

King Cobra (Ophiophagus hannah) Venom L-Amino Acid Oxidase Induces Apoptosis in PC-3 Cells and Suppresses PC-3 Solid Tumor Growth in a Tumor Xenograft Mouse Model

Abstract: King cobra (Ophiophagus hannah) venom L-amino acid oxidase (OH-LAAO), a heat stable enzyme, has been shown to exhibit very potent anti-proliferative activity against human breast and lung tumorigenic cells but not in their non-tumorigenic counterparts. We further examine its in vitro and in vivo anti-tumor activity in a human prostate adenocarcinoma (PC-3) model. OH-LAAO demonstrated potent cytotoxicity against PC-3 cells with IC50 of 0.05 µg/mL after 72 h incubation in vitro. It induced apoptosis as evidenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…The apoptotic effect of LAAOs from snake venoms has been reported by many authors, such as Lee et al (2014), Samel et al (2006), Zhang et al (2004), Alves et al (2008) and Ande et al (2008).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The apoptotic effect of LAAOs from snake venoms has been reported by many authors, such as Lee et al (2014), Samel et al (2006), Zhang et al (2004), Alves et al (2008) and Ande et al (2008).…”
Section: Resultsmentioning
confidence: 97%
“…Re-oxidation of FAD by molecular O 2 results, in turn, in the production of keto acids, ammonia and hydrogen peroxide (H 2 O 2 ) (Moustafa et al, 2006;Tan and Fung, 2009). The generated H 2 O 2 can induce (St abeli et al, 2004) and inhibit platelet aggregation (Sakurai et al, 2003;Naumann et al, 2011), induce endothelial injury (Du and Clemetson, 2002) and are involved in the apoptosis of various cell cells due to DNA damage Marcussi et al, 2013;Lee et al, 2014). Bothrops marajoensis is found in the plains of Maraj o Island in the State of Par a, Brazil and possibly along the coastal lowlands of the Amazon Delta, in Brazil (Cavalcante et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…The results indicated an apparent membrane rupture in MDCK cells at the highest concentrations studied ( Figure 1B), showing an increase in LDH release. Apoptosis caused by snake venoms is mediated by various different components, such as metalloprotease, phospholipase A2 and L-amino acid oxidase [4][5][6][7][8]. Several studies have confirmed the involvement of Bothrops and Bothropoides venom components in apoptosis [9,10].…”
Section: Resultsmentioning
confidence: 88%
“…In a study of the king cobra (Ophiophagus hannah) venom l-amino acid oxidase, Lee et al [32] reported that the heat-stable enzyme exhibited very potent anti-proliferative activity against human breast and lung tumorigenic cells, but not in their non-tumorigenic counterparts. They further reported that after eight weeks of treatment of mice samples with the isolated LAAOs, the enzyme markedly inhibited PC-3 tumours when compared to the control group.…”
Section: Amino Acid Oxidasesmentioning
confidence: 99%